A ROS‐based human‐robot interaction for indoor exploration and mapping - Achmad, Hendriyawan; Mohd Razali, Daud; Saifudin, Razali; Pebrianti, Dwi (IASE, 2016)
This paper proposes the methods how humans work with tele-operated to perform interaction with mobile robots in order to explore and build an indoor map by utilizing robotic software framework known as Robot Operating System (ROS). However, robotics researchers have limited time during the experiments with definite targets and ultimately there is no choice but to use an integration tools as software framework to avoid re-inventing the wheel. A ROS infrastructure tools are involving together from the file system level to the community level, enables independent decisions about development and implementation. This experiments focus on two major area; the way human delivers the targets coordinate to the robot and the way robot conducts SLAM as a feed back to the human related to current location and occupied map within ROS platform. Hector SLAM plays an important role in 2D localization using 2D LIDAR sensor which is needed by Octomap in order to construct 3D mapping simultaneously using Kinect sensor. The results showed that human-robot interaction using ROS-based tele-operated system for mapping task has able to satisfy and met the quality of the desired results in term of generate 3D map in unexplored area and less time consumption in term of large-scale service robot development.